2016
DOI: 10.1080/02667363.2016.1195341
|View full text |Cite
|
Sign up to set email alerts
|

How does Mindfulness training change the narratives of young people identified as having behavioural difficulties? An exploratory study

Abstract: Research investigating Mindfulness as an approach to intervention has generally taken a quantitative approach, focusing on outcomes rather than processes (Grossman, 2008). The purpose of this research was to develop understanding of how and why Mindfulness training might influence young people. The aim was to explore the changes in narratives that occur in young people following a Mindfulness intervention, in order to provide an understanding of how such an intervention might facilitate change. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Some studies claimed to be resource efficient (Bosnjak et al, 2017;Snape & Atkinson, 2017), whereas others were considered time-consuming (Chodkiewicz & Boyle, 2016;Toland & Boyle, 2008). Benefits of working systemically alongside school staff to support the CYP more broadly (Ardern, 2016;Yates & Atkinson, 2011) contrasted with logistical difficulties in therapeutic delivery (Weeks et al, 2017). Atkinson, 2017) are juxtaposed to distributed benefits to the wider school (Levine & Anshel, 2017;Squires & Caddick, 2012;Toland & Boyle, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies claimed to be resource efficient (Bosnjak et al, 2017;Snape & Atkinson, 2017), whereas others were considered time-consuming (Chodkiewicz & Boyle, 2016;Toland & Boyle, 2008). Benefits of working systemically alongside school staff to support the CYP more broadly (Ardern, 2016;Yates & Atkinson, 2011) contrasted with logistical difficulties in therapeutic delivery (Weeks et al, 2017). Atkinson, 2017) are juxtaposed to distributed benefits to the wider school (Levine & Anshel, 2017;Squires & Caddick, 2012;Toland & Boyle, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…All of the studies identified at least some positive impacts resulting from the therapeutic intervention. Eight reported favorable social/ emotional outcomes, such as increased optimism and improved self-concept (Ardern, 2016;Cole et al, 2012;Hannen & Woods, 2012;Kittles & Atkinson, 2009;Squires & Caddick, 2012;Weeks, Hill & Owen, 2017;Yates & Atkinson, 2011;Yeo & Choi, 2011). Four reported academic gains, such as improvements in reading skills (Bosnjak et al, 2017;Chodkiewicz & Boyle, 2016, Cockroft & Atkinson, 2017Toland & Boyle, 2008) and four identified improvements in behavioral measures, such as academic enabling behaviors (Briesch DuBois et al, 2017;Cryer & Atkinson, 2015;Levine & Anshel, 2011;Snape & Atkinson, 2017).…”
Section: Impact Of Therapeutic Interventionsmentioning
confidence: 99%